(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this article, we introduce the notion of cyclic α-admissible mapping with respect to θ with its special cases, which are cyclic α-admissible mapping with respect to θ^∗ and cyclic α^∗-admissible mapping with respect to θ. We present the notion of orthogonal (αθ−βF)-rational contraction and establish new fixed point results over orthogonal F-metric space. The study includes illustrative examples to support our results. We apply our results to prove the existence and uniqueness of solutions for second-order differential equations.